Pizza and Taco. 6, Dare to be scared! - Shaskan, Stephen (New York : Random House, 2023)
Besties Pizza and Taco are on a mission to prove they're not scared of anything, including scary movies and Ghost Peppers.
School Library Journal, October 2023
1.4
K-3
GN270L
Keywords: Best friends -- Comic books, strips, etc; Best friends -- Juvenile fiction; Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Pizza -- Comic books, strips, etc; Pizza -- Juvenile fiction; Tacos -- Comic books, strips, etc; Tacos -- Juvenile fiction; Fear -- Comic books, strips, etc; Fear -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Pizza -- Fiction; Tacos -- Fiction; Fear -- Fiction; Humorous stories; Humorous comics; Graphic novels; Comics (Graphic works)